2018
DOI: 10.1007/s40292-018-0252-5
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Renin–Angiotensin–Aldosterone System and Its New Components in Arterial Stiffness and Vascular Aging

Abstract: Many cardiovascular diseases present renin-angiotensin-aldosterone system (RAAS) hyperactivity as an important pathophysiological mechanism to be target in the therapeutic approaches. Moreover, arterial stiffness is currently considered as a new independent risk factor for cardiovascular disease in different clinical conditions, including hypertension and chronic kidney disease. In fact, excessive stimulation of angiotensin type 1 (AT1) receptors, as well as mineralocorticoid receptors, results in cellular gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 88 publications
0
28
0
10
Order By: Relevance
“…As identified in the protocols for vascular reactivity under in vitro AT 1 receptor blockade, these authors suggested that reduced NO and elevated ROS, due to AT 1 receptor activation could play a role in the genesis of vascular functional and structural remodelling in the rat model of iron‐overload. In fact, the mechanism by which drugs that inhibit the RAS attenuate or reverse vascular remodelling is related to the modulation of growth‐promoting, pro‐oxidant, and pro‐inflammatory actions of Ang II and thereby improving the arterial compliance, all independent of BP reduction (Brassard, Amiri, & Schiffrin, ; Janić, Lunder, & Sabovič, ; Neves, Cunha, Cunha, Gismondi, & Oigman, ; Ng et al, ; Shahin et al, ; Zhu et al, ). Consistent with these findings, the blockade of AT 1 receptors in vivo, was capable of preventing aortic deposition of collagen and stiffening also in the iron‐overload model.…”
Section: Discussionmentioning
confidence: 99%
“…As identified in the protocols for vascular reactivity under in vitro AT 1 receptor blockade, these authors suggested that reduced NO and elevated ROS, due to AT 1 receptor activation could play a role in the genesis of vascular functional and structural remodelling in the rat model of iron‐overload. In fact, the mechanism by which drugs that inhibit the RAS attenuate or reverse vascular remodelling is related to the modulation of growth‐promoting, pro‐oxidant, and pro‐inflammatory actions of Ang II and thereby improving the arterial compliance, all independent of BP reduction (Brassard, Amiri, & Schiffrin, ; Janić, Lunder, & Sabovič, ; Neves, Cunha, Cunha, Gismondi, & Oigman, ; Ng et al, ; Shahin et al, ; Zhu et al, ). Consistent with these findings, the blockade of AT 1 receptors in vivo, was capable of preventing aortic deposition of collagen and stiffening also in the iron‐overload model.…”
Section: Discussionmentioning
confidence: 99%
“…Показано, что артериальная гипертензия, являющаяся одним из основных факторов развития ДЭП, не только изменяет структуру церебральных сосудов, вызывая гипертрофию и ремоделирование сосудистой стенки, способствует развитию атеросклероза крупных сосудов и липогиалиноза мелких сосудов, но и может блокировать феномен функциональной гиперемии. Это сопровождается снижением прироста перфузии в теменной коре и таламусе при выполнении когнитивных тестов, что коррелирует с ухудшением их результатов [20][21][22].…”
Section: патогенезunclassified
“…23,24 Endothelial stiffness and whole vessel stiffness are also promoted by activation of the systemic and local reninangiotensin-aldosterone axis as well as vascular mineralocorticoid receptor activation and increased expression of angiotensin II type 1 receptors leading to vessel wall hypertrophy and fibrosis, which reduce arterial elasticity. 24,25…”
Section: Introductionmentioning
confidence: 99%
“…IR states and the resultant endothelial stiffness are also characterized by an imbalance between endothelial production of important opposing regulators of arterial stiffness, such as NO and endothelin‐1, whose levels are reduced and increased, respectively . Endothelial stiffness and whole vessel stiffness are also promoted by activation of the systemic and local renin‐angiotensin‐aldosterone axis as well as vascular mineralocorticoid receptor activation and increased expression of angiotensin II type 1 receptors leading to vessel wall hypertrophy and fibrosis, which reduce arterial elasticity …”
mentioning
confidence: 99%